sin²x - 2 sin x cos x - 3 cos²x = 0 | : cos²x
sin²x / cos²x - 2 sin x cos x / cos²x - 3 cos²x / cos²x = 0
tg²x - 2 tg x - 3 = 0
Замена: tg x = t
t² - 2t - 3 = 0
t₁ = -1
t₂ = 3
Обратная замена:
1) tg x = -1
x = arctg (-1) + πn, n ∈ Z
x = -π/4 + πn, n ∈ Z
2) tg x = 3
x = arctg (3) + πk, k ∈ Z
ответ: x = -π/4 + πn, n ∈ Z; x = arctg (3) + πk, k ∈ Z
########################
sin²x - 2 sin x cos x - 3 cos²x = 0 | : cos²x
sin²x / cos²x - 2 sin x cos x / cos²x - 3 cos²x / cos²x = 0
tg²x - 2 tg x - 3 = 0
Замена: tg x = t
t² - 2t - 3 = 0
t₁ = -1
t₂ = 3
Обратная замена:
1) tg x = -1
x = arctg (-1) + πn, n ∈ Z
x = -π/4 + πn, n ∈ Z
2) tg x = 3
x = arctg (3) + πk, k ∈ Z
ответ: x = -π/4 + πn, n ∈ Z; x = arctg (3) + πk, k ∈ Z
########################